Molecular characterization of Hepatitis B virus basal core promoter and precore region of isolates from chronic Hepatitis B patients - Israr Ahmad; Kafeel Ahmad (Journal of the Pakistan Medical Association, 2021)
Objective: The aim of this study was to analyze mutations in precore/core promoter region of HBV genome in chronic hepatitis B patients from three cities of Pakistan. Methods: A total of 50 treatment naïve chronic hepatitis B patients from Pakistan were selected. Viral load, HBeAg/antiHBe status, HBV ELISA and ALT levels were determined. Direct sequencing of BCP and PC region of HBV genome was carried out following a nested PCR approach. Phylogenetic tree was constructed using MEGA software version 6.0. Statistical analysis was carried out using SPSS version 16.0. Results: The G1896A precore stop codon mutation was detected in 19 (38%) isolates. The mutation was present in 17(34%) isolates from HBeAg negative patients and 2(4%) isolates from HBeAg positive patients. The Classic A1762T/G1764A double mutation was noted in 15 (30%) isolates. Mutation at position 1764 was observed in 12 (48%) samples. A rare G1764T mutation was also detected in 6 (12%) isolates. The CG1802-1803 mutation was detected in 47(94%) isolates. The T1858 mutation was detected in all 50 (100%) isolates. The GCAC Kozak sequence was present in 43(86%) isolates. The CAA1817-1819 mutation was observed in 49(98%) isolates and G1888 mutation was detected in 49(98%) isolates. Overall, 9(18%) isolates had wild-type sequences at all important loci including positions 1762,1764 and 1896. The pattern of sequences at genotype specific positions and phylogenetic tree revealed that majority of study isolates belonged to genotype D. Conclusions: Sequences results showed that precore region was comparatively more conserved than BCP region. Continuous...